HUBUNGAN KECERDASAN EMOSI DENGAN RESILIENSI AKADEMIK ANAK PANTI ASUHAN - Tarigan, Thomas Natalisa; br Karo, Selpi; br Tarigan, Sisri; Sinuraya, Sugito Firmanta (STP St. Bonaventura Medan, 2020)
This research was conducted to determine whether there is a relationship between emotional intelligence and academic resilience in the Orphanage children. The subjects of the study were 54 children from the Bethlehem Orphanage in Bandar Baru, Deli Serdang, North Sumatra. The research approach used is a combination of quantitative with qualitative, especially interviews. Quantitative research results show that emotional intelligence is positively and significantly correlated with academic resilience of orphanage children. Emotional intelligence contributed 50.2%. The results of interviews conducted with the leadership of the orphanage and the elder member support the findings